Identification of another module involved in the horizontal transfer of the Haemophilus genomic island ICEHin1056 - Juhas, M; Dimopoulou, I; Robinson, E; Elamin, A; Harding, R; Hood, D; Crook, D (2013)
A significant part of horizontal gene transfer is facilitated by genomic islands. Haemophilus influenzae genomic island ICE. Hin1056 is an archetype of a genomic island that accounts for pandemic spread of antibiotics resistance. ICE. Hin1056 has modular structure and harbors modules involved in type IV secretion and integration. Previous studies have shown that ICE. Hin1056 encodes a functional type IV secretion system; however, other modules have not been characterized yet. Here we show that the module on the 5' extremity of ICE. Hin1056 consists of 15 genes that are well conserved in a number of related genomic islands. Furthermore by disrupting six genes of the investigated module of ICE. Hin1056 by site-specific mutagenesis we demonstrate that in addition to type IV secretion system module, the investigated module is also important for the successful conjugal transfer of ICE. Hin1056 from donor to recipient cells. © 2013 Elsevier Inc.